Pengaruh Kandungan Serbuk Sekam Padi, Serbuk Kulit Kacang Tanah, dan Serat Ijuk Terhadap Kekuatan Impak dan Mikrostruktur Komposit Matriks Resin - Nurgiansyah, Rama; Muhamad Fitri (Jurnal Teknik Mesin Indonesia, 2025)
This study is driven by the utilization of organic materials of rice husk powder, peanut shell powder, and palm fiber for the needs of environmentally friendly composite materials. This research seeks to ascertain the largest percentage within the impact test resistance of each material and the characteristics of the composite microstructure. This research was conducted using the experimental test method at Mercu Buana University’s Mechanical Engineering Laboratory, where the examination is carried there was an utilizing the Charpy to test the impact method, while the microstructure characteristics were carried out using optical microscopy (OM). The experiment was employed in this investigation by dividing into 9 composition variations on the impact test specimen by manual molding using a specimen mold and drying it under sunlight for 1-2 hours, after which an impact test was conducted in order to assess the durability of the specimen and analyze the microstructure of the specimen. Based on the studies that have been conducted, the specimen with the highest toughness is combination B which has a toughness value of 20 kJ/m2